Study on the Potential Mechanism of Tonifying Kidney and Removing Dampness Formula in the Treatment of Postmenopausal Dyslipidemia Based on Network Pharmacology, Molecular Docking and Experimental Evidence - Li, Xuewen; Chen, Hongyan; Yang, Hongyan; Liu, Jian; Li, Yang; Dang, Yue; Wang, Jiajing; Wang, Lei; Li, Jun; Nie, Guangning (Frontiers in Endocrinology, 2022)
Background: Management of menopausal dyslipidemia is the main measure to reduce the incidence of cardiovascular disease in postmenopausal women. Tonifying Kidney and Removing Dampness Formula (TKRDF) is a traditional Chinese medicine (TCM) formula that ameliorates dyslipidemia in postmenopausal women. This study applied network pharmacology, molecular docking, and in vitro and in vitro experiments to investigate the underlying mechanism of TKRDF against postmenopausal dyslipidemia. Methods: Network pharmacology research was first conducted, and the active compounds and targets of TKRDF, as well as the targets of postmenopausal dyslipidemia, were extracted from public databases. Protein–protein interaction (PPI), Gene Ontology (GO), and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses were used to identify the potential targets and signaling pathways of TKRDF in postmenopausal dyslipidemia. Molecular docking was then performed to evaluate the combination of active compounds with principal targets. Finally, an ovariectomized rat model was used for the in vivo experiment and alpha mouse liver 12 (AML12) cells treated with palmitic acid were used for the in vitro experiment to provide further evidence for the research. Results: Based on network pharmacology analysis, we obtained 78 active compounds from TKRDF that acted on 222 targets of postmenopausal dyslipidemia. The analysis results indicated that IL6, TNF, VEGFA, AKT1, MAPK3, MAPK1, PPARG and PIK3CA, etc., were the potentially key targets, and the PI3K/AKT signaling pathway was the possibly crucial pathway for TKRDF to treat postmenopausal dyslipidemia. Molecular docking suggested that the active compounds have good binding activity with the core targets. The in vivo and in vitro experiments demonstrated that TKRDF ameliorates postmenopausal dyslipidemia by regulating hormone levels, inhibiting inflammation, promoting angiogenesis and inhibiting lipid synthesis, which appear to be related to TKRDF's regulation of the ERK1/2 and PI3K/AKT signaling pathways. Conclusion: This study clarified the active ingredients, potential targets, and molecular mechanisms of TKRDF for treating postmenopausal dyslipidemia. It also provided a feasible method to uncover the scientific basis and therapeutic mechanism for prescribing TCM in the treatment of diseases.